2013
DOI: 10.1590/s1983-14472013000300014
|View full text |Cite
|
Sign up to set email alerts
|

Náuseas, vômitos e qualidade de vida de mulheres com câncer de mama em tratamento quimioterápico

Abstract: The aim of this study was to assess the quality of life (QoL) of women with breast cancer during chemotherapy and to identify the incidence of nausea and vomiting during the treatment Data were assessed with the application of the instrument of the European Organization for Research and Treatment of Cancer, EORTC-QLQ-C30 Portuguese version and breast cancer module BR-23, which was applied before, in the middle and in the end of the treatment. The participants were 79 women, of which 93% had nausea and 87% had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
14

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 14 publications
(21 reference statements)
0
9
0
14
Order By: Relevance
“…Também há uma variedade metodológica nos estudos. As repetições ocorrem quando se trata de metodologias de pesquisa de tipo levantamento 15,18 , casocontrole 8,11 e estudos de método qualitativo com análise de conteúdo temática 13,14 . Destaca-se a presença de um estudo que se delineou utilizando uma abordagem qualiquanti 19 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Também há uma variedade metodológica nos estudos. As repetições ocorrem quando se trata de metodologias de pesquisa de tipo levantamento 15,18 , casocontrole 8,11 e estudos de método qualitativo com análise de conteúdo temática 13,14 . Destaca-se a presença de um estudo que se delineou utilizando uma abordagem qualiquanti 19 .…”
Section: Resultsunclassified
“…Nota-se que distúrbios de sono, em especial a insônia, são frequentes em indivíduos com câncer de mama, com prevalência maior do que na população em geral. É comum que pacientes oncológicos acabem por apresentar comportamentos irregulares no que diz respeito ao seu sono 11,18 .…”
Section: Resultsunclassified
“…Of the 79 women interviewed, 93% presented nausea and 87% vomiting. 9 In relation to the care practices the nurses in this study cited, however, the following care was indicated: fractionate meals, avoid prolonged fasting, increase water intake, and give preference to foods that give you more pleasure. Some nonpharmacological approaches to relieve nausea and vomiting can be used, such as small, frequent meals.…”
Section: It's a Process It's An Effect The Chemotherapy Causes In Fmentioning
confidence: 87%
“…It is important to highlight the importance of the professional's look at each patient, offering alternatives to make the chemotherapeutic process less shocking and uncomfortable. 9 Among the other complaints the interviewed nurses reported, peripheral neuropathy was also cited. In a study of 244 chemotherapy patients' charts, only 20 of these patients presented peripheral neuropathy.…”
Section: It's a Process It's An Effect The Chemotherapy Causes In Fmentioning
confidence: 99%
“…No estudo realizado por Gozzo et al (2013), das 79 mulheres com câncer de mama em tratamento quimioterápico, 93% apresentaram náuseas e 87% vômitos pelo menos uma vez durante o tratamento e a qualidade de vida, que foi avaliada por meio do instrumento European…”
Section: Consequênciasunclassified